A CROSS-SECTIONAL STUDY ON FACTORS ASSOCIATED WITH CERVICAL CANCER SCREENING PRACTICES IN REPRODUCTIVE-AGE WOMEN. - Oraon, Bullu Priya; Singh, Shashi Bala (Student's Journal of Health Research Africa, 2024)
Background Cervical cancer is still a major worldwide public health problem. Early identification can result in prompt interventions and lower death rates. The objective of the study was to find out what factors affect women of reproductive age's cervical cancer screening (CCS) habits. Methods The study included 260 volunteers in all, ages 15 to 49. A pre-tested structured questionnaire covering sociodemographic traits, knowledge, attitudes, invitations from healthcare providers, aspects of sexual and reproductive health, and CCS practices was used to gather data. To evaluate relationships between variables, descriptive statistics, adjusted odds ratios, and bivariable logistic regression analysis were performed. Results The study showed that 72.5% of participants had heard of cervical cancer, with 58.1% correctly identifying its association with HPV. However, only 41.2% were aware of cervical cancer screening methods, though 76.9% expressed willingness to undergo screening if recommended. Approximately 54.6% received healthcare provider invitations for screening, among whom 68.3% underwent screening. Nearly half (48.5%) reported a history of STIs, with only 22.3% having undergone previous CCS. Barriers to screening included lack of awareness (38.1%) and fear of the procedure (29.5%). Conclusion Factors influencing CCS practices among reproductive-age women include awareness, healthcare provider invitation, and history of STIs. Healthcare provider invitation significantly influenced screening uptake, highlighting the importance of provider engagement in promoting screening services. Recommendations Targeted interventions should focus on enhancing awareness, addressing barriers, and increasing healthcare provider engagement to improve CCS uptake among reproductive-age women.